MOLECULAR DIVERSITY STUDY USING SSAP MARKERS IN PIGEONPEA (CAJANUS CAJAN L. MILLSP.) - PRAKASH G. PATIL,; M. BYRE GOWDA,; IKECHUKWU O. AGBAGWA,; KHELA RAM SOREN,; R. RAMACHANDRA,; H. E. SHASHIDHAR, (The Bioscan, 2015)
In the present study, based on in silico homology search SSAP markers were developed from one of the active Cajanus cajan retrotransposon element (CcRT8) and employed for molecular diversity study among 30 pigeonpea genotypes belonging to five different gene pools. Total four primer combinations were screened, which produced 156 bands of which 149 (95.50%) bands were polymorphic with an average of 37.2 polymorphic bands per primer combination. The average polymorphism information content (PIC) 0.26 and gene diversity (H^) 0.32 were found higher for primer combinations screened. These results indicated CcRT8 element showed higher insertional polymorphism in the pigeonpea genome. The Jaccard coefficients ranged from 0.16 to 0.96 suggesting a broad genetic base across the gene pools. However, within cultivars coefficients ranged from 0.69-0.96 revealing a narrow genetic base and these results confirmed earlier findings. Cluster analysis showed grouping of genotypes mainly on the basis of gene pools used. The present study suggested two genetically distant genotypes BRG 3 and ICP 15701, which could be potential donors for resistance breeding and for introgressing of novel genes into pigeonpea cultivars. Here, we have successfully demonstrated in silico search based development of SSAP markers for studying molecular diversity among pigeonpea genotypes.